Pengaruh Literasi Keuangan Syariah terhadap Keputusan Mahasiswa S-1 Unisba dalam Menggunakan Produk Bank Syariah - Delvi Delviana Saragi; Dewi Rahmi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The potential for the development of Islamic banks which are part of the existence of a sharia economy is not accompanied by a high proportion of market share and a high sharia financial inclusion index. Islamic financial literacy is present as an effort to Muslim community decisions to use Islamic Bank products, one of which is through priority targets, namely students. The purpose of this study is to analyze the influence of the three indicators of Islamic financial literacy variables as well as the most dominant indicators influencing the decisions of Unisba undergraduate students to use Islamic Bank products. The method used in this research is quantitative and analytical model namely the binary logistic regression model. The data collection technique used a questionnaire and the population of Unisba undergraduate students. The sampling thechnique was used is purposive sampling. The results of this study indicate that the three indicators of the Islamic financial literacy variable have a positive and significant effect on the decision to use Islamic bank products. In addition, according to the coefficient value in the logistic regression analysis, it shows that the ability indicator has the largest coefficient value so that it becomes the most dominant indicator in influencing the decisions of Unisba undergraduate students in using Islamic Bank products. Abstrak. Potensi perkembangan Bank Syariah yang menjadi bagian dari eksistensi ekonomi syariah tidak diiringi dengan proporsi pangsa pasar dan indeks inklusi keuangan syariah yang tinggi. Literasi keuangan syariah hadir sebagai salah satu upaya untuk mendorong keputusan masyarakat muslim menggunakan produk Bank Syariah, salah satunya melalui sasaran prioritas yaitu kalangan mahasiswa. Tujuan dari penelitian ini yaitu menganalisis pengaruh ketiga indikator variabel literasi keuangan syariah serta indikator yang paling dominan mempengaruhi keputusan mahasiswa S-1 Unisba menggunakan produk Bank Syariah. Metode yang digunakan dalam penelitian ini adalah kuantitatif dan model analisis yaitu model regresi logistik biner. Teknik pengumpulan data menggunakan kuesioner dan populasi mahasiswa S-1 Unisba. Teknik penarikan sampel menggunakan teknik purposive sampling. Hasil dari penelitian ini menunjukkan bahwa ketiga indikator dari variabel literasi keuangan syariah berpengaruh positif dan siginifikan terhadap keputusan menggunakan produk bank syariah. Selain itu, menurut nilai koefisien dalam analisis regresi logistik menunjukkan bahwa indikator kemampuan mempunyai nilai koefisien terbesar sehingga menjadi indikator paling dominan dalam mempengaruhi keputusan mahasiswa S-1 Unisba dalam menggunakan produk Bank Syariah.